Valuing water from social, economic and environmental perspective - Shatanawi M.; Naber S. (Dialogues on Mediterranean water challenges: Rational water use, water price versus value and lessons learned from the European Water Framework Directive, 2011)
The increasing demand on water due to the growth of both the population and economy has put strong pressure on water quality and quantity. Water is therefore increasingly being valued as an economic resource. The price of water depends on quantity and quality as well as on the behavior of people and market. The value of water for society, people's health and the environment are important factors that should be considered in the valuation process. Water in sufficient quantity and good quality for drinking and sanitation to meet basic needs, is a human right. Water has been treated as an economic good as stated in the 1992 Dublin statement: water has an economic value in all its competing uses and should be recognized as an economic good. This is different from water pricing when pricing is intended to recover the full costs of infrastructure, management and operation. This may lead to economic pricing of water, which will damage the interests of the poor and will make irrigated agriculture unfeasible. Valuing water for domestic purposes in Egypt using different valuation techniques has shown the limits of the end-users' willingness to pay. Water pricing policy in Jordan is aimed at recovering the cost of operation and maintenance and at the same time at water conservation.
3. MELIA Workshop Water Value Impacts on the Mediterranean Water Policies, 2009/03/21-23, Istanbul (Turkey); 4. MELIA Workshop Benchmarking Exercise and Recommendations on the Application of the Water Framework Directive, 2010/03/21-26, Amman (Jordan)